The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Multiscale drivers of arthropod functional guilds in rice agroecosystems: Evaluating the roles of climatic, landscape, and management factors - Yu-Pin Lin; Pei-Chen Lin; Shafira Wuryandani; Chun-Chia Liu; Chiao-Ming Lin; Chi-Wei Tsai; Chi-Lun Huang; Chuan-Kai Ho; Gerard H. Ros (Agriculture, Ecosystems & Environment, 2026)

Chlorpyrifos exposure induces inflammatory and immune dysregulation: An integrative in silico and in vitro analysis - Chen-Yu Chiang; Shih-Pin Chen; Ci-Wen Luo; Chun-Hung Su; Shiuan-Shinn Lee; Wen-Ying Chen; Chun-Jung Chen; Ching-Chi Tseng; Pin-Tzu Chen; Yin-Che Lu; Yu-Hsiang Kuan (Pesticide Biochemistry and Physiology, 2026)

Regulating interface charge separation to unlock photocatalytic non-radical pathways: Construction of BiOCl/COF S-scheme heterojunction for efficient antibiotic remediation - Hailan Qin; Siyuan Di; Min Liu; Qiuyue Zhang; Pin Chen; Zihan Li; Shukui Zhu (Journal of Cleaner Production, 2026)

Integrative single-cell sequencing and environmental metabarcoding reveals genetic complexity and hidden diversity of the dinoflagellate Tripos (Dinophyceae) - Yingchao Li; Xianliang Huang; Haina Du; Xiangxiang Ding; Zhiyuan Gong; Po Teen Lim; Chui Pin Leaw; Nansheng Chen (Harmful Algae, 2026)

Targeting the NOX4/NLRP inflammasome axis confers protection by isoliquiritigenin against H2O2-induced synovial inflammation - Yu-Chun Chang; Wei-Wen Kuo; Yen-Pin Chen; Shih-Wen Kao; Dennis Jine-Yuan Hsieh; Tsung-Jung Ho; Chia-Hua Kuo; Chien-Yao Fu; Chih-Yang Huang; Shinn-Zong Lin (Chemico-Biological Interactions, 2026)

Global gap-free aerosol optical depth reconstruction based on the fusion of satellite and reanalysis data - Zheng Wang; Wencai Zhang; Tingting Xie; Yuxin Wang; Min Qiao; Tseng Chun-Pin; Xiaoxian Chen; Tianhao Gong (Advances in Space Research, 2026)

Elevated CO2 and temperature reshape soybean chemistry and drive physiological and life-history trade-offs in the beet webworm Loxostege sticticalis - Jingxian Zhou; Shuqi Ren; Pin Li; Sandhya Samarasinghe; Xingfu Jiang; Guijun Wan; Fajun Chen (Journal of Pest Science, 2026)

Protected areas on international borders show uneven conservation outcomes - Rachakonda Sreekar; Hoong Chen Teo; Tiantian Zhang; Jiajia Liu; Aakash Lamba; Jun Ying Lim; Lian Pin Koh; Sean Jing Wen Ng; Janice Ser Huay Lee; James E. M. Watson; Yiwen Zeng (Conservation Biology, 2026)
Border protected areas (BPAs) are national protected areas that are immediately adjacent to a country's border or span two or more countries; they are characterized by distinctive opportunities and pressures. They play a critical role in protecting carbon‐rich ecosystems, conserving endangered biodiversity, reducing cross‐border environmental threats, and promoting peace and cooperation. At the same time, compared with other protected areas within the same country, BPAs may be particularly vulnerable to asymmetric enforcement, cross‐border leakage, conflict, and weak institutional coordination. Using a pixel‐level propensity score matching approach, we conducted the first global assessment of forest loss in BPAs relative to counterfactuals in nonborder protected areas within the same country. We found that compared with nonborder protected areas, most BPAs (81%) experienced lower or similar forest loss rates, preventing the loss of 112,036 ha of forest and ∼3.69 MtCO 2 e/year in emissions between 2013 and 2022. However, the remaining 19% of BPAs experienced significantly higher forest loss than their counterfactuals, resulting in the loss of 87,657 ha and additional emissions of ∼2.85 MtCO 2 e/year. Importantly, BPA underperformance was not driven solely by lower border protection feasibility as larger reserve size and closer proximity to urban centers were also associated with higher forest loss. Drivers of forest loss in underperforming BPAs varied regionally: agriculture expansion dominated in Africa and Asia; regulatory mismatches in timber regulations were most important in Europe; and wildfire risk was a key factor in North America. We further identified mainland Southeast Asia and the Congo Basin as urgent border conservation hotspots, where high deforestation pressure threatens both endangered species and carbon‐rich forests. Thus, BPA underperformance is geographically concentrated and not pervasive. Targeted regional interventions would enhance cross‐border cooperation, mobilize sustainable financing, and strengthen governance structures, while also facilitating the effective integration of BPAs into global biodiversity and climate policy frameworks.

Copper/nickel-based bimetallic heterostructures anchored nitrogen-doped porous carbon for high-energy lithium and sodium-ion-based supercapatteries - Eswaran Narayanamoorthi; Cheng-Sao Chen; Haidee Mana-ay; Mani Govindasamy; Pin-Yi Chen (Fuel, 2026)

Effects of dietary rumen-protected bile acids on muscle fiber composition and drip loss in Hu sheep (Ovis aries): insights from transcriptomic and metabolomic analyses - Zhe Wang; Manman Hou; Dan Hu; Jie Huang; Qi Liu; Pin Song; Yue Chen; Pengnan Chen; Yuyang Yin; Aizhi Cao; Yufeng Li; Yingdong Ni (Food Bioscience, 2026)

Poly(lactic-co-glycolic acid) (PLGA)-based vaccine delivery systems for fish: physicochemical properties, immunological mechanisms, and applications - Shu-Chun Chuang; Yi-Chen Lin; Ya-Shuan Chou; Shang-Pin Liu; Shao-Wen Hung; Ti-Chun Chang; Chung-Hwan Chen; Chung-Da Yang (Fish & Shellfish Immunology, 2026)

Cyprinid herpesvirus 2 (CyHV-2) ORF53 inhibits NF-κB signalling by targeting p65 degradation - Chuan Yun Zhang; Zheng Liu; An Ning Pang; Jia Yi Li; Bo Li; Nan Li; Lan Hao Liu; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Self-healing chitosan-catechol hydrogel with tailored self-assembled fibrillar or micellar structures for biomedical applications - Pin-Yu Chen; Yuxuan Zhang; Shan-hui Hsu (Carbohydrate Polymers, 2026)

Unique synthesis of Tantalum carbide incorporated with functionalized Halloysite nanotube for the highly sensitive electrochemical detection of Marbofloxacin in milk products - Mahalakshmi Kannan; Haidee Mana-ay; Pin-Yi Chen; Adel El-marghany; Mani Govindasamy (Applied Clay Science, 2026)

A digital-enabled circular recovery system for post-consumer inhalers: Linking material recovery, behaviour, and carbon reduction - Huong Thanh Hoang; Luong Cao Tung Son; Yu-Fen Huang; Ren-Hao Pan; Phuong Truc Nguyen Le; I-Chun Chuang; Huang-Chi Chen; Hung-Pin Tu; Chih-Hsing Hung; Da-Wei Wu (Journal of Cleaner Production, 2026)

Mapping climate-conditioned PM2.5 response under climate change in Taiwan using a high-resolution Geo-AI model - Pei-Yi Wong; Wei-Lun Hsu; Chieh-Ying Chen; Chien-Fei Chen; Chia-Wei Hsu; Shih-Chun Candice Lung; Ta-Chih Hsiao; Chia-Pin Yu; Wan-Yu Liu; Pau-Chung Chen; Wei Jie Seow; Chien-Hao Sung; et al. (Journal of Environmental Management, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Assessing the impact of climate variability on exposure indices of Portunid crabs in the Southern East China sea - Irene Chia Ling Lim; Yan-Lun Wu; Wei-Pin Hsu; Muhamad Naimullah; Wei-Yu Lee; Lu-Chi Chen; Kuo-Wei Lan (International Journal of Remote Sensing, 2026)

Kinetically enhanced AgNPs/CeNi-LDH heterojunction for sensitive quantification of NO2− using a thumb−sized portable sensing interface - Harikrishnan Sathya; Devi Akalya Balamurugan; Gaber E. Eldesoky; Mani Govindasamy; Pin-Yi Chen (Chemical Engineering Journal, 2026)

Inhibiting pyruvate carboxylase as a potential therapeutic strategy for alleviating rheumatoid arthritis - Szu-Wei Huang; Hui-Chun Yu; Hsien-Bin Huang; Pin-Chen Chen; Ming-Chi Lu (Inflammopharmacology, 2026)

BRI3 Orchestrates Lipid Metabolism and Autophagy in Glioblastoma: Implications for Tumor Cell Resilience - Jun Chen; Pin Zuo; Situo Kuang; Ping Li; Xiaoquan Li; Dong Zhan (Biochemical Genetics, 2026)

Design Rules for Robust Coronary Artery Segmentation: A Systematic Analysis of Dataset Size, Windowing, Architectures, and Vessel Geometry - Ming-Hui Hung; Yu-Wei Chiang; Hao-Yun Liu; Han-Hsuan Chu; Yu-Sen Huang; Pin-Yi Chiang; Hsin-Ming Chen; Tzung-Dau Wang; Shyh-Jye Chen; Wen-Jeng Lee (Annals of Biomedical Engineering, 2026)

Age-stratified genomic analyses reveal population-specific genetic determinants of exceptional longevity in Taiwan - Ming-Shun Hsieh; Shu-Min Yang; Shu-Hui Liao; Chayanika Goswami; Pei-Hsuan Wu; Tzu-Hung Hsiao; Yi-Ming Chen; Sung-Yuan Hu; Chorng-Kuang How; Tzu-Pin Lu; Amrita Chattopadhyay (GeroScience, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Machine learning and spatial regression approaches to estimating willingness to pay for ecosystem services in Jakarta and Taoyuan - Shafira Wuryandani; Yu-Pin Lin; Pei-Chen Lin; Dirk S. Schmeller; Gerard H. Ros (Ecosystem Services, 2026)

Social behavior of masked palm civet in an urban habitat - Po-Jun Chuang; Pin Xuan Lim; Shan-Min Chen; Pin-Huan Yu; Wei-Ting Liu; Hui-Yun Tseng (Mammal Research, 2026)

Development of an artificial intelligence (AI) marine scientific research model: The case of marine science and technology policy and its legitimate practice in Taiwan - Juei-Cheng Jao; Chiao-Wen Lin; Pin-Chien Chen; Yi-Cheng Chang; Yi-Juen Chen; Wen-Hong Liu (Marine Policy, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

High ambient temperature during pregnancy and offspring cerebral palsy: A population-based case-control study in California - Haoran Zhuo; Joshua L. Warren; Giselle Bellia; Pin Wang; Kai Chen; Zeyan Liew; Tormod Rogne (Environmental Research, 2026)

Development and field application of an integrated three-phase greenhouse gas monitoring system in smart shrimp aquaculture with biofloc-based carbon mitigation - Cheng Yuan Kuo; Tzong Yueh Chen; Pin Han Chen (Aquacultural Engineering, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

MHC II system of mandarin fish (Siniperca chuatsi): Gene identification, expression analysis and transcriptional regulation - Jing Hou; Lu Qi; Ran Cao; Lan Hao Liu; Shan Nan Chen; Pin Nie (Aquaculture, 2026)

Evaluating post-fire watershed response to varying burn severity and precipitation regimes using fully-distributed and integrated hydrologic models - Zhi Li; Bing Li; Peishi Jiang; Glenn E. Hammond; Pin Shuai; Faria T. Zahura; Ethan T. Coon; Xingyuan Chen (Journal of Hydrology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Hydrothermal acid leaching process with ultra-high efficiency for vanadium from spent catalyst - Quanxian Hua; Junyang Ma; Pin Xu; Shu Zhang; Jingjing Rong; Zehao Chen (Minerals Engineering, 2025)

Detection of Marteilioides chungmuensis in cultured Portuguese oyster (Crassostrea angulata) in southern Taiwan - I-wen Chen; Chieh-Hao Wu; Yi-Pin Lu; Yu-Ju Lin (Fish & Shellfish Immunology, 2025)

Visible light driven highly selective oxidation of HMF coupled with H2 evolution via bimetal-doped synergism on ZnIn2S4 nanosheets - Yachen Hu; Wei Jiang; Zijun Zhang; Qinqin Jiang; Yawen Jiang; Lang Sun; Panjing Xu; Yanling Chang; Chuanqiang Wu; Ziming Fan; Meiling Wang; Zhou Chen; et al. (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Seismic evidence for magmatism-driven mud volcanism in the northern continental margin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Marine and Petroleum Geology, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Electroactive biofilm enhances synergistic degradation of sulfamethoxazole and roxarsone in actual livestock wastewater: extracellular electron transfer drives metabolic network remodeling - Pin Peng; Xinyu Yan; Lixiang Chen; Xiang Li; Huiying Yang; Yijing Miao; Feng Zhao (Environmental Research, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Redefining the monitoring of antioxidants: Interfacial charge redistribution in SrTiO3@GCN nanocomposite for improved electrochemical detection of propyl gallate in food matrices - Gopika Meenakumari Gopakumar; Aiswarya Bindu; Beena Saraswathyamma; Amel Ayari-Akkari; Ali Akremi; Pin-Yi Chen; Mani Govindasamy (Innovative Food Science & Emerging Technologies, 2025)

Achieving high specific capacitance via cobalt doping over Nb4C3Tx with boron nitride composite for supercapacitor application - Nikhil Prabhakar; M. Lakshmi Narayanan; Haidee Mana-ay; N. Ponpandian; C. Viswanathan; Pin-Yi Chen (Fuel, 2025)

Continuous cell lines from kidney and spleen of Japanese eel, Anguilla japonica, with capacity for antiviral immune response - Xiaoling Zhou; Dongli Li; Yanting Chen; Pin Nie; Bei Huang; Wenshu Huang (Fish & Shellfish Immunology, 2025)

Adverse pulmonary effects and metallic characteristic of size-resolved welding fumes in human lung epithelial BEAS-2B cells - Pin-Hao Qiu; Chia-Hua Lin; Yen-Ping Peng; Ku-Fan Chen; Yi-Chun Chen; Yung-Chang Lin; Chia-Hsiang Lai (Environmental Toxicology and Pharmacology, 2025)

Paper meets polymer: Efficiently manufacturing hybrid microfluidics for membrane-based applications - Phong Vi Lam; Chien-Ming Hsieh; Pin-Chuan Chen; Pai-Shan Chen (Chemical Engineering Journal, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Freshwater microalgae-mediated engineered nanoparticles: Sustainable approach for heavy metals remediation - Manish Sutradhar; Raju Kumar Sharma; Gobinda Dey; Uttara Sukul; Koyeli Das; Md. Taharia; Pin-Yun Lin; Shafiqa Ali; Chin-Wen Wang; Chien-Yen Chen (Bioresource Technology, 2025)

Performance and mechanism investigation of CO2 capture by novel ternary MEA/tertiary amine/sulfolane biphasic solvents - Guangjie Chen; Guangying Chen; Liuyi Yin; Fei Li; Li Sze Lai; Wee Horng Tay; Swee Pin Yeap; Lin Jin (International Journal of Greenhouse Gas Control, 2025)

Genomic and phylogenetic analyses of the domoic acid biosynthesis genes in the benthic diatom Nitzschia navis-varingica (Bacillariophyceae) - Zongmei Cui; Hui Wang; Po Teen Lim; Suh Nih Tan; Yuichi Kotaki; Chui Pin Leaw; Nansheng Chen (Harmful Algae, 2025)

Applications, life cycle assessment, and circular economy of bamboo torrefaction for sustainability: A state-of-the-art review - Wei-Hsin Chen; Pin-Chun Liang; Wei-Yi Wang; Pen-Chi Chiang; Jiří Ryšavý; Jakub Čespiva; Jo-Shu Chang (Bioresource Technology, 2025)

Growth and reproductive performance of reciprocal crossbred sex-linked dwarf and non-dwarf Taiwan Country chickens - Samkelo Mlandvo Motsa; Tsung-Che Tu; Szu-Hung Chen; Pin-Chi Tang; Chih-Feng Chen (Tropical Animal Health and Production, 2025)

Hydraulic heterogeneity estimation with transient hydraulic tomography and convolutional encoder-decoder neural network - Yu-Kai Chen; Jui-Pin Tsai; Bo-Tsen Wang; Chia-Hao Chang (Stochastic Environmental Research and Risk Assessment, 2025)

Lung cancer screening completion among patients using decision aids: a systematic review and meta-analysis - Alexander Antigua-Made; Sabrina Nguyen; Ali Rashidi; Wen-Pin Chen; Argyrios Ziogas; Gelareh Sadigh (Cancer Causes & Control, 2025)
Purpose Utilization of lung cancer screening (LCS) among eligible patients remains low at 16% in 2022. In this systematic review and meta-analysis we assessed the (a) LCS completion rate, and (b) intention to complete LCS, among patients who receive patient decision aids (PDAs). Methods PubMed, Cochrane, Scopus, CINAHL, and Web of Science were searched for articles published in English between 1 January 2011, and 28 February 2023. Two independent reviewers selected randomized controlled trials and prospective cohort studies that reported PDA interventions targeting either LCS completion rate or intention to complete LCS. Quality appraisal and data extraction were performed independently by 2 reviewers using the National Heart, Lung, and Blood Institute quality assessment tool. A random-effects model meta-analysis was performed. Reporting followed the Preferred Reporting Items for Systematic Review and Meta-analyses guidelines. Results Thirteen studies with 2,277 total participants (51.5% male) were included. The pooled LCS completion rate across all follow-up periods (range, 1–6 months) was 40% (95% confidence interval [CI], 15–65%) with an I 2 of 97% for heterogeneity. Pooled intention to complete LCS among patients who received PDA across all follow-up periods (same day to 3 months) was 57% (95% CI, 34% to 80%) with significant heterogeneity (I 2 ) of 96% ( p < 0.0001). No publication bias was identified. Conclusions LCS completion and intention to complete LCS among patients who use PDAs is high. Our findings support the need to implement PDAs in clinical practice which could further facilitate shared decision-making and improve LCS uptake among eligible patients.

Impact of Emergent Macrophyte Mowing on an Aquatic Insect Community in Urban Ponds: A Case Study in an Artificial Wetland in Southeast Asia - Pin-Yuan Chen; Xiaoli Dong; John Durand; Hsiao-Wei Yuan (Wetlands, 2025)
Urban ponds increase biodiversity by providing essential habitats, mitigating heat, and serving as refuges for aquatic species. Macrophyte management, particularly mowing, plays a crucial role in altering vegetation structure and influencing water quality factors. However, the effects on aquatic insect communities remain unclear, as previous studies have not explicitly differentiated between direct and indirect effects. Additionally, little is known about how the total effect of mowing varies over time and with increasing water temperature. To address this gap, we conducted paired treatment experiments (with/without macrophyte mowing) from April to September in a Southeast Asian urban wetland. Using Bayesian structural causal modeling, we quantified both the total and direct effects of mowing on aquatic insect communities. Our results show that mowing primarily increases aquatic insect abundance via indirect pathways, with impacts varying by family and season. In summer, mowing increased the abundance of midge larvae (Chironomidae), likely due to their tolerance to high water temperature, whereas damselfly larvae (Coenagrionidae) require cooler conditions. Conversely, during spring and fall, mowing decreased the abundance of both midge larvae and damselfly larvae. Mowing also increases water temperature and dissolved oxygen, further affecting aquatic insect abundance. Overall, our research provides a novel mechanistic understanding of how emergent macrophyte mowing influences aquatic insect communities, addressing key methodological limitations in previous studies. These findings can inform more effective macrophyte management strategies to enhance aquatic biodiversity in urban ecosystems.

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Development of a colorimetric loop-mediated isothermal amplification (cLAMP) assay for the rapid and visual detection of Aeromonas dhakensis infection in aquaculture - Suat Moi Puah; Wei Ching Khor; Yen Ching Lim; Kyaw Thu Aung; Tien-Tien Vicky Lau; Chen Chen Yong; Po Teen Lim; Chui Pin Leaw; Kek Heng Chua (Aquaculture, 2025)

Contributions of urbanization and population growth to changes in urban flood exposure in recent decades - Ziyi Tang; Pin Wang; Yao Li; Chaohui Chen; Yihan Lou; Tangao Hu (Sustainable Cities and Society, 2025)

The mafic–ultramafic roots of a magmatic arc from the East Kunlun Orogen, NW China - Zhi-Xiong Zhao; Guo-Chen Dong; M. Santosh; Di-Cheng Zhu; Hui-Lei Kong; Shu-Jun Lü; Pin-Yan Zhong (Gondwana Research, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Insights into the efficient activation of peracetic acid by Fe/Co−NBC for florfenicol degradation: Performance, mechanism, and toxicity evaluation - Haitian Song; Yan Qin; Yajie Qian; Xiaoqian Chen; Pin Gao (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

Comparative analysis of phytochemical and antioxidant potential in traditional medicinal plants: Insights from solvent-based extractions - Shafiqa Ali; Haibat Ali; Ashiq Hussain; Gobinda Dey; Chin-Wen Wang; Md Taharia; Pin-Yun Lin; Raju Kumar Sharma; Ping-Gune Hsiao; Chien Yen Chen (Food Bioscience, 2025)

Transcriptome analysis of head kidney and liver in grass carp (Ctenopharyngodon idella) symptomatically or asymptomatically infected with Flavobacterium columnare - Yong Jin; Nan Li; Shan Nan Chen; Yi Shan Lu; Zhen Gan; Pin Nie (Fish & Shellfish Immunology, 2025)

Corrigendum to “N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater” [Chem. Eng. J. 491 (2024) 151763] - Pin Peng; Lixiang Chen; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2025)

Enhanced SERS performance through defect-guided growth of 2D/3D AuAg nanoplates for chemical sensing and cellular imaging applications - Kuan-Wen Liu; Pei-Yu Sie; Hsi-Ying Chen; Fong-I Ho; Po-Sheng Huang; Pin Chieh Wu; Mei-Yi Liao (Analytica Chimica Acta, 2025)

Recent progress in optimization of RANS turbulence models for accurate urban airflow and contaminant dispersion simulations - Sumei Liu; Longhui Xu; Bingqian Chen; Zhipeng Deng; Pin Li; Runmin Zhao; Qingyan Chen (Sustainable Cities and Society, 2025)

Metal ion-induced multi-layer coatings improves gastrointestinal resistance of Lactiplantibacillus plantarum and biosafety evaluation - Yanming Ren; Shuifang Mao; Pin Chen; Xingqian Ye; Jinhu Tian (Food Hydrocolloids, 2025)

Fault materials and creep characteristics in mudstone areas: A case study of Chegualin Fault in southwestern Taiwan - Pin-Hao Chen; Yen-Hua Chen; Ming-Chih Hsieh; Yan-Wei Huang; Chien-Che Huang; Wei-Teh Jiang; Jey-Jau Lee; Yao-Chang Lee; Hwo-Shuenn Sheu (Engineering Geology, 2025)

A Comprehensive Investigation of Physics-Informed Learning in Forward and Inverse Analysis of Elastic and Elastoplastic Footing - Xiao-Xuan Chen; Pin Zhang; Zhen-Yu Yin (Computers and Geotechnics, 2025)

Immune response to polystyrene microplastics: Regulation of inflammatory response via the ROS-driven NF-κB pathway in zebrafish (Danio rerio) - Jincheng Pei; Shannan Chen; Qingxia Ke; Anning Pang; Mengmeng Niu; Nan Li; Jiayi Li; Zhi Wang; Hongjuan Wu; Pin Nie (Aquatic Toxicology, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Global research landscape and trends in Toxoplasma gondii from 2003 to 2022: A bibliometric analysis - Shi-Jie Fan; Ming Pan; Chen-Yang Xia; Pin Yang; Si-Yang Huang (Veterinary Parasitology, 2025)

Development of a real-time dynamic inundation risk assessment approach on paddy fields during typhoons: Exploration of adaptation strategies and quantification of risks - Bing-Chen Jhong; Feng-Wen Chen; Ching-Pin Tung (Journal of Environmental Management, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Effect of safflower seed oil on the molecular structural and enzyme hydrolysis properties of maize starch-lipid complexes - Wen Tan; Qinjun Zhang; Pin Chen; Qingqing Sun; Changqing Wei; Xinwen Xu; Natthawuddhi Donlao; Jinhu Tian (Food Chemistry, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Impact of bacterial cell concentration on microbial-mediated cerium carbonate precipitation for efficient heavy metal removal: Insights from adsorption isotherm, kinetics, and thermodynamics - Md. Taharia; Koyeli Das; Uttara Sukul; Hung-Chun Chao; Pritam Banerjee; Gobinda Dey; Raju Kumar Sharma; Pin-Yun Lin; Tung-Che Hung; Chien-Yen Chen (Bioresource Technology, 2025)

Inter-alpha Inhibitor Proteins Modulate Microvascular Endothelial Components and Cytokines After Exposure to Hypoxia–Ischemia in Neonatal Rats - Liam M. Koehn; Kevin V. Nguyen; Richard Tucker; Yow-Pin Lim; Xiaodi Chen; Barbara S. Stonestreet (Molecular Neurobiology, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Microplastic types dominate the effects of bismuth oxide semi-conductor nanoparticles on their transport in saturated quartz sand - Lin Xu; Shaoyan Lv; Quanyuan Chen; Pin Gao; Genyao Gu; Yongxia Wang; Xiaopeng Min; Hyunjung Kim; Li Cai (Journal of Hazardous Materials, 2025)

Enrichment and characterization of foodborne fungal spores by ferric ion-based surface-assisted laser desorption/ionization mass spectrometry - Tzu-Ling Yang; Chih-Wei Chen; Noor Hidayat Abu Bakar; Pin-Chen Pan; Po-Hung Cheng; Yu-Chie Chen (Food Chemistry, 2025)

Effects of forest bathing and the influence of exposure levels on cognitive health in the elderly: Evidence from a suburban forest recreation area - Jittakon Ramanpong; Chen Tsao; Jie Yin; Chih-Da Wu; Yu-Chih Huang; Chia-Pin Yu (Urban Forestry & Urban Greening, 2025)

Comprehensive interpretation of hillslope subsurface flow – An analytical approach to hillslopes with complex geometry - Bao-Ming Jin; Xin Yang; Kwan Tun Lee; Pin-Chun Huang; Peng Lin; Lanlan Gao; Lo-Ya Chen (Journal of Hydrology, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

Metal ions-mediated concerted electron-proton transfer enables catalytic oxidation of phenolic contaminants by permanganate - Tiansheng Chen; Pin Xie; Yanghai Yu; Xiaoguang Duan; Yuankui Sun; Xiaohong Guan (Water Research, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Comparison of UV based advanced oxidation processes (UV/H2O2, UV/NaClO, and UV/Na2S2O8) for inactivating Uronema marinum in marine water - Xuan Chen; Pin Gan; Kunling Huang; Fangyu Liang; Tianhao Wu; Xudong Li; Yuanyuan Zhang (Journal of Water Process Engineering, 2025)

Rheology, stability, and physicochemical properties of NaOH-tannic acid solvent for β-chitin dissolution - Shang-Ta Wang; Po-Jou Huang; Szu-Kai Chen; Chia-Rui Shen; Yi-Pin Chen; Min-Lang Tsai (Food Hydrocolloids, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Ordered self-assembled monolayer improved the buried interface of wide bandgap perovskite for efficient and stable semi-transparent solar cells - Peiran Hou; Shenghan Hu; Yuxi Zhang; Junye Pan; Min Hu; Jiahui Chen; Bingxin Duan; Li Wan; Pin Lv; Yanqing Zhu; Shengqiang Xiao; Yi-Bing Cheng; et al. (Chemical Engineering Journal, 2025)

Unlocking anaerobic digestion potential via extracellular electron transfer by exogenous materials: Current status and perspectives - Xinyu Yan; Pin Peng; Xiang Li; Xudong Zhou; Lixiang Chen; Feng Zhao (Bioresource Technology, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Rich molecular diversity of ribosomal RNA genes in Pseudo-nitzschia species (Bacillariophyceae) revealed through single-strain high throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Chui Pin Leaw; Nansheng Chen (Algal Research, 2025)

Sedimentary Signatures of Super Typhoon Haiyan: Insight from Core Record in South China Sea - Yu-Huang Chen; Chih-Chieh Su; Pai-Sen Yu; Ta-Wei Hsu; Sheng-Ting Hsu; Hsing-Chien Juan; Yuan-Pin Chang; Yu-Fang Ma; Shye-Donq Chiu (Journal of Marine Science and Engineering, 2024)
Sedimentary records of event deposits are crucial for regional natural disaster risk assessments and hazard history reconstructions. After Super Typhoon Haiyan passed through the South China Sea in 2013, five gravity cores were collected along the typhoon path in the southern South China Sea basin (>3800 mbsl). The results showed that Super Typhoon Haiyan deposits with clear graded bedding are preserved at the top of all cores. The thickness of the typhoon layers ranges from 20 to 240 cm and is related to changes in typhoon intensity. The lack of river-connected submarine canyon systems limited the transportation of terrestrial sediments from land to sea. Super Typhoon Haiyan-induced large surface waves played an important role in carrying suspended sediment from the Philippines. The Mn-rich layers at the bottom of the typhoon layers may be related to the soil and rock composition of the Palawan region, which experienced tsunami-like storm surges caused by Super Typhoon Haiyan. These Mn-rich layers may serve as a proxy for sediment export from large-scale extreme terrigenous events. This study provides the first sedimentary record of extreme typhoon events in the deep ocean, which may shed light on reconstructing regional hazard history.

Evaluation and mitigation of potentially toxic elements contamination in mangrove ecosystem: Insights into phytoremediation and microbial perspective - Gobinda Dey; Jyoti Prakash Maity; Pritam Banerjee; Raju Kumar Sharma; Koyeli Das; Gopalakrishnan Gnanachandrasamy; Chin-Wen Wang; Pin-Yun Lin; Shan-Li Wang; Chien-Yen Chen (Marine Pollution Bulletin, 2024)

Unveiling the interaction and combined effects of multiple metals/metalloids exposure to TNF-α and kidney function in adults using bayesian kernel machine regression and quantile-based G-computation - Kuei-Hau Luo; Hung-Pin Tu; Yong-Chuan Chung; Min-Hsin Huang; Chen-Cheng Yang; Tzu-Hua Chen; Cheng-Hong Yang; Hung-Yi Chuang (Journal of Trace Elements in Medicine and Biology, 2024)

Enhancing degradation of antibiotic-combined pollutants by a hybrid system containing advanced oxidation and microbial treatment, a review - Pin Peng; Xinyu Yan; Xudong Zhou; Lixiang Chen; Xiang Li; Yijing Miao; Feng Zhao (Journal of Hazardous Materials, 2024)

Astragaloside IV alleviates diabetic nephropathy by modulating the gut-kidney axis and AMPK/PI3K/AKT pathway - Pin Gong; Hui Long; Qian Yang; Rui Zhou; Wenjuan Yang; Fuxin Chen; Jianwu Xie; Yanni Zhao; Hongbo Xu (Food Bioscience, 2024)

The Effect of Platelet Fibrin Plasma (PFP) on Postoperative Refractory Wounds: Physiologically Concentrated Platelet Plasma in Wound Repair - Lu Fan; Ying Zhang; Xiankun Yin; Silu Chen; Pin Wu; Tianru Huyan; Ziyang Wang; Qun Ma; Hua Zhang; Wenhui Wang; Chunyan Gu; Lu Tie; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Taiwan’s mysterious mollusks: a deep dive into the cryptic hybridization of Pomacea canaliculata and Pomacea maculata - Pritam Banerjee; Nalonda Chatterjee; Kathryn A. Stewart; Jung-Sheng Chen; Gobinda Dey; Jyoti Prakash Maity; Raju Kumar Sharma; Chin-Wen Wang; Pin-Yun Lin; Kuan Hsien Lee; Chien-Yen Chen (Evolutionary Ecology, 2024)

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Terrestrial support of wetland food webs via a dissolved inorganic carbon pathway - Junna Wang; John R. Durand; Sharon P. Lawler; Pin‐Yuan Chen; Xiaoli Dong (Limnology and Oceanography, 2024)
Studies of terrestrial support of aquatic food webs have focused primarily on terrestrial organic matter (t‐OM) directly used by animal and microbial consumers. However, dissolved inorganic carbon (DIC) released from t‐OM might also support aquatic primary producers, a key resource for zooplankton and upper trophic levels. Using 2‐yr 13 C measurements of algae, zooplankton, terrestrial detritus, sediments, dissolved and particulate organic matter from six seasonal wetlands, we found that in January when algal concentration was low, zooplankton used t‐OM directly or heterotrophic microbes that decompose t‐OM, but in March and May zooplankton was mainly supported by algae as their basal resources, and the algae used DIC derived from the mineralization and methanogenesis of t‐OM, suggesting the DIC pathway of terrestrial support of aquatic food webs. The decomposition of abundant t‐OM from both bed sediments and water column caused high concentrations of DIC. Despite uptake by algae, about half of DIC produced in January and March ended up as emissions to the atmosphere in the form of CO 2 . This finding revealed the dual roles of t‐OM in maintaining the productivity and stability of aquatic food webs and in contributing to global carbon emissions. This duality poses challenges for simultaneously mitigating carbon emissions and conserving biological communities in seasonal wetlands. Finally, wide seasonal differences in δ 13 C in DIC (−12.4‰ to 6.7‰) were observed, mainly driven by air–water CO 2 exchange and photosynthesis, suggesting that 13 C may be a powerful tool to investigate carbon cycling in shallow, temporary freshwater ecosystems that are widespread but understudied.

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Possible toxification mechanisms of acute and chronic pentachlorophenol to Montipora digitata: Limitation of energy supply and immunotoxicity - Lan Luo; Pengfei Xue; Xuan Chen; Pin Gan; Xiaoli Li; Kefu Yu; Yuanyuan Zhang (Science of The Total Environment, 2024)

Optimizing parameter learning and calibration in an integrated hydrological model: Impact of observation length and information - Peishi Jiang; Pin Shuai; Alexander Y. Sun; Xingyuan Chen (Journal of Hydrology, 2024)

Treatment of arsenic-contaminated groundwater with a novel iron oxide/carbon composite as the adsorbent - Hung-Hsiang Chen; Yu-Chen Chang; Wei-Kuo Wei; Yung-Pin Tsai; Chih-Chi Yang; Ku-Fan Chen (Water, Air, & Soil Pollution, 2024)

Predicting increments in heavy metal contamination in farmland soil - Jieh-Haur Chen; Meng-Fen Yeh; Jui-Pin Wang; Hsi-Hsien Wei (Environment, Development and Sustainability, 2024)

Impact of polystyrene nanoplastics on apoptosis and inflammation in zebrafish larvae: Insights from reactive oxygen species perspective - Jincheng Pei; Shannan Chen; Li Li; Kailun Wang; Anning Pang; Mengmeng Niu; Xueyun Peng; Nan Li; Hongjuan Wu; Pin Nie (Science of The Total Environment, 2024)

Bisphenol M inhibits mouse oocyte maturation in vitro by disrupting cytoskeleton architecture and cell cycle processes - Huilei Chen; Yang Liu; Yue Huang; Pin Zhang; Danli Du; Wenhua Yu; Caiyun Wu; Hongzhen Ruan; Ping Zhou; Zhiming Ding; Huifen Xiang (Reproductive Toxicology, 2024)

Structural characterization and hypoglycemic activity of Cordyceps sinensis polysaccharide (CSP-3) - Pin Gong; Yingying Ke; Xiaojuan Wang; Hui Long; Wenjuan Yang; Jing Wang; Nan Li; Yanni Zhao; Fuxin Chen; Yuxi Guo (Food Bioscience, 2024)

Effects of Attachment Design and Aligner Material on Mandibular Canine Distal Bodily Movement in Aligner Treatment - Pin-Yu Chen; Heng-Li Huang; Jian-Hong Yu; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2024)
Purpose Dental crowding is a result of a mismatch between tooth size and arch dimensions, which leads to malocclusion; treatment often involves premolar extraction before orthodontic alignment. Clear aligners are limited in their ability to achieve canine distal bodily movement, a common orthodontic maneuver. This study investigated the impacts of attachment design and aligner material on the efficacy of canine distal bodily movement. Methods A finite element analysis was conducted to examine the impact of various attachment designs and two aligner materials, thermoplastic polyurethanes/polycarbonate (TPU/PC) and polyethylene terephthalate glycol-modified (PETG), on mandibular canine distal bodily movement. The investigation focused on the biomechanical responses in the periodontal ligament (PDL) and surrounding alveolar bone. Results Attachment configuration exerted a strong influence on mandibular canine movement. Vertically oriented attachment pairs positioned mesially (mesial occlusal–mesial cervical) resulted in the most effective canine distal bodily movement, followed by a rectangular attachment. TPU/PC aligners induced slightly higher principal stresses in the PDL and von Mises stress and strain in the surrounding alveolar bone compared with PETG aligners; however, the difference was negligible, amounting to less than 6%. Conclusion Attachment design, specifically vertically oriented pairs positioned mesially (mesial occlusal–mesial cervical), was determined to be the crucial factor influencing the efficacy of canine distal bodily movement. The choice of aligner material (TPU/PC or PETG) has minimal impact on this orthodontic procedure.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

Comparison of the inactivation of Uronema marinum in mariculture by UV/chlorine, UV/monochloramine, and UV/chlorine dioxide: Efficiency, mechanism and feasibility - Pin Gan; Xuan Chen; Yuanyuan Zhang; Xudong Li; Fangyu Liang; Tianhao Wu; Pengfei Xue; Kefu Yu (Journal of Water Process Engineering, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Analytical solution for transient radial interaction between energy piles and soils: Thermo-elastic cavity expansion analysis - He Yang; Pei-Zhi Zhuang; Pin-Qiang Mo; Hai-Sui Yu; Xiaohui Chen (Geomechanics for Energy and the Environment, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Casein/butyrylated dextrin nanoparticles and chitosan stabilized bilayer emulsions as fat substitutes in sponge cakes - Han Tao; Xiao-Han Fang; Pin Chen; Bao-Qiu Yang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

N-doped carbon dots/g-C3N4 photoexcitation simultaneously enhanced the microbial degradation of nitrate and oxytetracycline in a low C/N ratio aquaculture wastewater - Pin Peng; Lixiang Chen.; Xinyu Yan; Rui Bai; Bob Adyari; Xudong Zhou; Feng Zhao (Chemical Engineering Journal, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Fulvic acid-mediated efficient anaerobic digestion for kitchen wastewater: Electrochemical and biochemical mechanisms - Xinyu Yan; Pin Peng; Xudong Zhou; Xiang Li; Lixiang Chen; Feng Zhao (Water Research, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

1300-m-High gas plume from pockmarks in the north Nansha waters, South China sea - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Jinfeng Ma; Zhuangcai Tian; Changliang Chen (Marine and Petroleum Geology, 2024)

Molecular cloning and functional analyses of C–C motif chemokine ligand 3 (CCL3) in mandarin fish Siniperca chuatsi - Xiao Liu; Jia Xiang Ji; An Ning Pang; Li Li; Pin Nie; Li Qiang Zhang; Ke Wei Zeng; Shan Nan Chen (Fish & Shellfish Immunology, 2024)

Chlorpyrifos-induced suppression of the antioxidative defense system leads to cytotoxicity and genotoxicity in macrophages - Yin-Che Lu; Chen-Yu Chiang; Shih-Pin Chen; Yu-Wei Hsu; Wen-Ying Chen; Chun-Jung Chen; Yu-Hsiang Kuan; Sheng-Wen Wu (Environmental Toxicology and Pharmacology, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

The health risk reduction of PM2.5 via a green curtain system in Taiwan - Yi Hsing Chang; Ting-Hsuan Chen; Hsin-Ying Chung; Hsi-Yu Hsiao; Pin-Chieh Tseng; Yu-Chun Wang; Shih-Chun Candice Lung; Huey-Jen Su; Yaw-Shyan Tsay (Building and Environment, 2024)

Biogeochemistry of sedimentary organic matter in the Yongjiang River estuary in the southern part of Hangzhou Bay, China, since the Late Pleistocene - Dongqin Huang; Xiaolong Li; Zilong Li; Pei Sun Loh; Jianxiong Hu; Jianfang Chen; Yuan-Pin Chang; Chin-Wen Yang; Qin Gao (Journal of Oceanology and Limnology, 2024)

Extensive intragenomic variations of the 18S rDNA V4 region in the toxigenic diatom species Pseudo-nitzschia multistriata revealed through high-throughput sequencing - Hui Wang; Kuiyan Liu; Ziyan He; Yang Chen; Zhangxi Hu; Weizhou Chen; Chui Pin Leaw; Nansheng Chen (Marine Pollution Bulletin, 2024)

The establishment and evaluation of a swine model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Lutao Xie; Yi Chen; Wang Du; Xuelin Yang; Wanjuan Liu; Peixin Shangguan; Jiefeng Xu; Pin Lan (Toxicon, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Photochemical oxidation of VOCs and their source impact assessment on ozone under de-weather conditions in Western Taiwan - Manisha Mishra; Pin-Hsin Chen; Guan-Yu Lin; Thi-Thuy-Nghiem Nguyen; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Shih-Heng Shih; Ciao-Wei Jhang; Chuen-Jinn Tsai (Environmental Pollution, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Streamlining regular liquid chromatography with MALDI-TOF MS and NMR spectroscopy using automatic full-contact splitless spotting interface and flash-tap fractioning collection - Chi-Minh Truong; Yung-Cheng Jair; Hong-Po Chen; Wei-Chih Chen; Yi-Hsin Liu; Pin-Chuan Chen; Pai-Shan Chen (Analytica Chimica Acta, 2024)

Microbial-mediated oxidative dissolution of orpiment and realgar in circumneutral aquatic environments - Xiaoxu Sun; Duanyi Huang; Yuqing Huang; Max Häggblom; Mohsen Soleimani; Jiayi Li; Zheng Chen; Zhenyu Chen; Pin Gao; Baoqin Li; Weimin Sun (Water Research, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Intersubject representational similarity analysis uncovers the impact of state anxiety on brain activation patterns in the human extrastriate cortex - Po-Yuan A. Hsiao; M. Justin Kim; Feng-Chun B. Chou; Pin-Hao A. Chen (Brain Imaging and Behavior, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

An overview of microplastic pollution in the environment over the megacity of Shanghai during 2013–2022 - Peikun Yuan; Yang Wang; Xiaoqian Chen; Pin Gao (Science of The Total Environment, 2024)

Boosting algicidal efficiency of Alteromonas sp. FDHY-CJ against Skeletonema costatum through fermentation optimization - Pin Lv; Xinguo Shi; Qianqian Wang; Yuying Zhong; Yisong Guo; Jianfeng Chen (Protist, 2024)

Management of the designed risk level of urban drainage system in the future: Evidence from haining city, China - Yihan Lou; Pin Wang; Yao Li; Luoyang Wang; Chaohui Chen; Jiahui Li; Tangao Hu (Journal of Environmental Management, 2024)

Bifunctional drug delivery system with carbonic anhydrase IX targeting and glutathione-responsivity driven by host-guest amphiphiles for effective tumor therapy - Jiawei Zhou; Yamin Li; Lutao Wang; Pin Lv; Miao Chen; Feijian Xiao; Tian Si; Jun Tao; Bo Yang (Carbohydrate Polymers, 2024)

Assessment of sediment transport in Luxiapuqu watershed using RUSLE-TLSD and InSAR techniques: Yarlung Tsangpo River, China - Hao-Shuang Chen; Ling Lan; Yi-Pin Nie; Yu-Ge Wang; Xie-Kang Wang (Environmental Science and Pollution Research, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

Dual role of birnessite on the modulation of acid production and reinforcement of interspecific electron transfer in anaerobic digestion - Xinyu Yan; Lixiang Chen; Pin Peng; Fan Yang; Liping Dai; Han Zhang; Feng Zhao (Science of The Total Environment, 2024)

Physiological and psychological responses to transitions between urban built and natural environments using the cave automated virtual environment - Di Chen; Jie Yin; Chia-Pin Yu; Shengjing Sun; Charlotte Gabel; John D. Spengler (Landscape and Urban Planning, 2024)

Short-term variation in Mars atmospheric methane concentrations driven by barometric pumping - Ronald W. Klusman; Yangcheng Luo; Pin Chen; Michael A. Mischna; Yuk L. Yung (Icarus, 2024)

Subsurface structures and nature of seafloor mounds in the northern South China Sea margin: Implications for Mesozoic hydrocarbon exploration - Junhui Yu; Pin Yan; Yanlin Wang; Guangjian Zhong; Changliang Chen (Geomorphology, 2024)

Activation of peroxymonosulfate by sewage sludge-derived biochar to promote short-chain fatty acid production during sludge anaerobic fermentation - Jinling He; Qingchen Wu; Nan Jiang; Ai Zhang; Lin Wang; Xiang Li; Gang Xue; Hong Chen; Pin Gao (Chemical Engineering Journal, 2024)

Efficient degradation of fluoroquinolone antibiotics in the landfill leachate by sludge biochar activated peracetic acid: Radical vs non-radical process - Zilin Zhou; Yan Yang; Gang Xue; Yang Yu; Jiabin Chen; Pin Gao; Yajie Qian (Chemical Engineering Journal, 2024)

Emission characteristics of naphthalene from ship exhausts under global sulfur cap - Chin-Ko Yeh; Fu-Ming Tzu; Po-Yang Chen; Hsueh-Chen Shen; Chung-Shin Yuan; Chitsan Lin; Han-Pin Pu; Huu Hao Ngo; Xuan-Thanh Bui (Science of The Total Environment, 2023)

Branch distribution pattern and anticoagulant activity of a fucosylated chondroitin sulfate from Phyllophorella kohkutiensis - Di Lan; Jiali Zhang; Xiaolei Shang; Lijuan Yu; Chen Xu; Pin Wang; Lige Cui; Nanqi Cheng; Huifang Sun; Jianing Ran; Le Sha; Ronghua Yin; et al. (Carbohydrate Polymers, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Inactivation of Heterosigma akashiwo under UV/peroxydisulfate advanced disinfection system in marine waters - Xuan Chen; Kunling Huang; Pin Gan; Lan Luo; Kefu Yu; Yuanyuan Zhang; Yunfeng Pang; Pengfei Xue (Chemosphere, 2023)

Strategies analysis for improving SWAT model accuracy and representativeness of calibrated parameters in sediment simulation for various land use and climate conditions - Li-Chi Chiang; Pin-Chih Shih; Chih-Mei Lu; Bing-Chen Jhong (Journal of Hydrology, 2023)

Manipulation of crystallization nucleation and thermal degradation of PLA films by multi-morphologies CNC-ZnO nanoparticles - Ya-Fang Yan; Xiao-Bo Liang; Yan-Long Feng; Lin-Fang Shi; Rui-Pin Chen; Jian-Zhong Guo; Ying Guan (Carbohydrate Polymers, 2023)

Insight interactions of engineered nanoparticles with aquatic higher plants for phytoaccumulation, phytotoxicity, and phytoremediation applications: A review - Uttara Sukul; Koyeli Das; Jung-Sheng Chen; Raju Kumar Sharma; Gobinda Dey; Pritam Banerjee; Md. Taharia; Cheng-I Lee; Jyoti Prakash Maity; Pin-Yun Lin; Chien-Yen Chen (Aquatic Toxicology, 2023)

Seasonal Disparities of Human Health Risk and Particle-Bound Metal Characteristics Associated with Atmospheric Particles in a Fishery Harbor - Cheng-Yun Tsai; Yen-Ping Peng; Chia-Hua Lin; Ku-Fan Chen; Chia-Hsiang Lai; Pin-Hao Qiu (Archives of Environmental Contamination and Toxicology, 2023)

Integrating anaerobic acidification with two-stage forward osmosis concentration for simultaneously recovering organic matter, nitrogen and phosphorus from municipal wastewater - Siyi Chen; Zunaira Habib; Zhiwei Wang; Pin Zhao; Weilong Song; Xinhua Wang (Water Research, 2023)

Performance and degradation pathway of florfenicol antibiotic by nitrogen-doped biochar supported zero-valent iron and zero-valent copper: A combined experimental and DFT study - Zheng Tang; Yifan Kong; Yan Qin; Xiaoqian Chen; Min Liu; Lu Shen; Yanming Kang; Pin Gao (Journal of Hazardous Materials, 2023)

TAT-PEP Alleviated Cognitive Impairment by Alleviating Neuronal Mitochondria Damage and Apoptosis After Cerebral Ischemic Reperfusion Injury - Pin Zhao; Jiapo Zhang; JianKe Kuai; Liya Li; Xuying Li; Namin Feng; Hailiang Du; Chen Li; Qiang Wang; Bin Deng (Molecular Neurobiology, 2023)
Paired immunoglobulin-like receptor B (PirB) was identified as a myelin-associated inhibitory protein (MAIP) receptor that plays a critical role in axonal regeneration, synaptic plasticity and neuronal survival after stroke. In our previous study, a transactivator of transcription-PirB extracellular peptide (TAT-PEP) was generated that can block the interactions between MAIs and PirB. We found that TAT-PEP treatment improved axonal regeneration, CST projection and long-term neurobehavioural recovery after stroke through its effects on PirB-mediated downstream signalling. However, the effect of TAT-PEP on the recovery of cognitive function and the survival of neurons also needs to be investigated. In this study, we investigated whether pirb RNAi could alleviate neuronal injury by inhibiting the expression of PirB following exposure to oxygen–glucose deprivation (OGD) in vitro. In addition, TAT-PEP treatment attenuated the volume of the brain infarct and promoted the recovery of neurobehavioural function and cognitive function. This study also found that TAT-PEP exerts neuroprotection by reducing neuronal degeneration and apoptosis after ischemia–reperfusion injury. In addition, TAT-PEP improved neuron survival and reduced lactate dehydrogenase (LDH) release in vitro. Results also showed that TAT-PEP reduced malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) activity and reduced reactive oxygen species (ROS) accumulation in OGD-injured neurons. The possible mechanism was that TAT-PEP could contribute to the damage of neuronal mitochondria and affect the expression of cleaved caspase 3, Bax and Bcl-2. Our results suggest that PirB overexpression in neurons after ischaemic-reperfusion injury induces neuronal mitochondrial damage, oxidative stress and apoptosis. This study also suggests that TAT-PEP may be a potent neuroprotectant with therapeutic potential for stroke by reducing neuronal oxidative stress, mitochondrial damage, degeneration and apoptosis in ischemic stroke.

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

The combined effects of North Atlantic Oscillation and Western Pacific teleconnection on winter temperature in Eastern Asia during 1980–2021 - Ziqun Zhang; Hongyan Cui; Baoxu Chen; Hong Cai; Pin Li (Acta Oceanologica Sinica, 2023)

Increasing contribution of urban greenery to residential real estate valuation over time - Hoong Chen Teo; Tze Kwan Fung; Xiao Ping Song; Richard N. Belcher; Kelly Siman; Ian Z.W. Chan; Lian Pin Koh (Sustainable Cities and Society, 2023)

Source-apportionment and spatial distribution analysis of VOCs and their role in ozone formation using machine learning in central-west Taiwan - Manisha Mishra; Pin-Hsin Chen; Wilfredo Bisquera; Guan-Yu Lin; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Ciao-Wei Jhang; Ci-Jhen Wu; Chuen-Jinn Tsai (Environmental Research, 2023)

Discrete element modelling of thermal penetration test with heating and cooling - Pin-Qiang Mo; Jing Hu; Yu-Chen Hu; Kuan-Jun Wang; Abolfazl Eslami; Liu Gao (Computers and Geotechnics, 2023)

Arginase from Priestia megaterium and the Effects of CMCS Conjugation on Its Enzymological Properties - Yu Liang Jiao; Pin Quan Shen; Shu Fang Wang; Jing Chen; Xiang Hong Zhou; Gui Zhen Ma (Current Microbiology, 2023)

Predicting the acoustic characteristics of seafloor sediments containing cold spring carbonate rocks - Yuhang Tian; Lei Wu; Dapeng Zou; Zhong Chen; Yongjun Jiang; Pin Yan; Chaoyan Fan (Frontiers in Marine Science, 2023)
The acoustic and physical properties of two valuable marine cold spring carbonate rock samples gathered from the Chaoshan Depression in the South China Sea were measured. The Wyllie time-average equation was applied to analyze the measured sound speeds and their trend under different porosities, and the sound speeds of marine cold spring carbonate rocks were found to be consistent with those of terrestrial carbonate rocks. The Voigt model, Reuss model, and Voigt-Reuss-Hill model were used to predict the characteristics of the sound speed for four states of seafloor sediments containing cold spring carbonate mineral particles or rocks. For these four states of marine cold spring carbonate mineral particles existing on or in seafloor sediments, the sound speed and reflection coefficient of a mixture of seafloor surface sediments containing cold spring carbonate mineral particles or rocks decrease with an increase in the volume ratio of the seafloor sediment. This method for predicting the reflection coefficient provides evidence to explain the high and low reflection coefficients observed in Chirp sub-bottom profiles of cold spring seepage areas.

Association between ambient air pollutant interaction with kidney function in a large Taiwanese population study - Wei-Yu Su; Da-Wei Wu; Hung-Pin Tu; Szu-Chia Chen; Chih-Hsing Hung; Chao-Hung Kuo (Environmental Science and Pollution Research, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Ecofriendly removal of Lead, Cadmium and Arsenic along with turbidity from contaminated water using natural reservoir clay (NRC) and S. pasteurii derived urease - Jyoti Prakash Maity; Yung-Ping Chen; Jirawadee Promsri; Yi-Hsun Huang; Raju Kumar Sharma; Yu-Hui Chen; Pin-Yun Lin; Marut Tangwattanachuleeporn; Kulwara Poolpol; Tsung-Hsien Chen; Chien-Yen Chen (Desalination, 2023)

Impact of industrial development and machinery and transport equipment on natural resources in South Africa - Zhaohui Qin; Yuchen Pan; Pin Peng; Hailin Chen; Winnie Kudzai Mazheti (Resources Policy, 2023)

Outcomes between endoscopic-assisted minimally invasive surgery and conventional craniotomy in spontaneous intracerebral hemorrhage - Yi-Ying Hsieh; Bo-An Chen; Kuan-Hao Fu; Yi-Hsien Kuo; Ying-Yun Chen; Jiun-Lin Yan; Pin-Yuan Chen (Neurophysiology, 2023)

Detection of live SARS-CoV-2 virus and its variants by specially designed SERS-active substrates and spectroscopic analyses - Jaya Sitjar; Jiunn-Der Liao; Han Lee; Huey-Pin Tsai; Jen-Ren Wang; Chien-Hsiung Chen; Hao Wang; Bernard Haochih Liu (Analytica Chimica Acta, 2023)

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

High-Fat Diet Exacerbates Autistic-Like Restricted Repetitive Behaviors and Social Abnormalities in CC2D1A Conditional Knockout Mice - Yu-Chiao Wang; Chin-Hao Chen; Cheng-Yi Yang; Pin Ling; Kuei-Sen Hsu (Molecular Neurobiology, 2023)

Origin of a giant fuzzy reflection zone and its implication for natural gas exploration in the southwestern Qiongdongnan Basin of the South China Sea - Junhui Yu; Pin Yan; Yanlin Wang; Yan Qiu; Guanghong Tu; Changliang Chen (Journal of Oceanology and Limnology, 2023)

Discovery of pockmarks in the Zengmu Basin, southern South China Sea and the implication - Yanlin Wang; Guanghong Tu; Junhui Yu; Pin Yan; Yongbin Jin; Changliang Chen; Jie Liu (Journal of Oceanology and Limnology, 2023)

The Effect of Microplastics-Plants on the Bioavailability of Copper and Zinc in the Soil of a Sewage Irrigation Area - XinYue Ma; XiaoLi Ma; Pin Chen (Bulletin of Environmental Contamination and Toxicology, 2023)

Cu/Al2O3 aerogels for high-efficiency and rapid iodide elimination from water - Xinyu Zhou; Pin Mao; Huiran Jin; Wanxia Huang; Aotian Gu; Kaiwei Chen; Shan Yun; Jing Chen; Yi Yang (Journal of Hazardous Materials, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Nitrogen addition alleviates drought effects on water status and growth of Moso bamboo (Phllostachys edulis) - Xi-Pin Wu; Shirong Liu; Junwei Luan; Yi Wang; Xiaomin Gao; Chen Chen (Forest Ecology and Management, 2023)

A novel Cu nanoporous aerogel for high-efficient immobilization of iodide in water - Xinyu Zhou; Huiran Jin; Shan Yun; Wanxia Huang; Pin Mao; Jing Chen; Yi Yang (Chemical Engineering Journal, 2023)

Carbon emission reduction policy with privatization in an oligopoly model - Junlong Chen; Chaoqun Sun; Yajie Wang; Jiali Liu; Pin Zhou (Environmental Science and Pollution Research, 2023)

Geophysical evidence for a serpentine mud volcano in the relict slow-spreading center of the South China Sea - Yanlin Wang; Pin Yan; Junhui Yu; Guanghong Tu; Jun Wang; Yan Qiu; Changliang Chen (Tectonophysics, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Investigating relationships between landscape patterns and surface runoff from a spatial distribution and intensity perspective - Luoyang Wang; Hao Hou; Yao Li; Jing Pan; Pin Wang; Ben Wang; Jie Chen; Tangao Hu (Journal of Environmental Management, 2023)

Fabrication of a core-shell porphyrin-based magnetic covalent organic framework for effective extraction of PCPs in a wide polarity range - Tao Ning; Siyuan Di; Zihan Li; Haokun Zhang; Zhangdi Peng; Hucheng Yang; Pin Chen; Yue Bao; Yixin Zhai; Shukui Zhu (Analytica Chimica Acta, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Local thermal effect of power-on setting on monopolar coagulation: a three-dimensional electrothermal coupled finite element study - Yung-Chuan Chen; Yuan-Kun Tu; Yi-Jung Tsai; Yueh-Pin Tsai; Chih-Kun Hsiao (Medical & Biological Engineering & Computing, 2022)

Analyzing spatial variance of urban waterlogging disaster at multiple scales based on a hydrological and hydrodynamic model - Luoyang Wang; Yao Li; Hao Hou; Yan Chen; Jinjin Fan; Pin Wang; Tangao Hu (Natural Hazards, 2022)

When conventional methods fall short: identification of invasive cryptic Golden Apple Snails (Pomacea canaliculata; P. maculata) using environmental DNA - Pritam Banerjee; Kathryn A. Stewart; Gobinda Dey; Raju Kumar Sharma; Jyoti Prakash Maity; Michael W. Y. Chan; Kuo Pin Chang; Tsung-Hsien Chen; Chia-Ti Hsu; Chien-Yen Chen (Hydrobiologia, 2022)

Large‐scale reforestation can increase water yield and reduce drought risk for water‐insecure regions in the Asia‐Pacific - Hoong Chen Teo; Srivatsan V. Raghavan; Xiaogang He; Zhenzhong Zeng; Yanyan Cheng; Xiangzhong Luo; Alex M. Lechner; Matthew J. Ashfold; Aakash Lamba; Rachakonda Sreekar; Qiming Zheng; Anping Chen; et al. (Global Change Biology, 2022)
Large‐scale reforestation can potentially bring both benefits and risks to the water cycle, which needs to be better quantified under future climates to inform reforestation decisions. We identified 477 water‐insecure basins worldwide accounting for 44.6% (380.2 Mha) of the global reforestation potential. As many of these basins are in the Asia‐Pacific, we used regional coupled land‐climate modeling for the period 2041–2070 to reveal that reforestation increases evapotranspiration and precipitation for most water‐insecure regions over the Asia‐Pacific. This resulted in a statistically significant increase in water yield ( p

CDK1 promotes the proliferation of melanocytes in Rex rabbits - Yingying Dai; Shuaishuai Hu; Shaocheng Bai; Jiali Li; Naisu Yang; Pin Zhai; Bohao Zhao; Yang Chen; Xinsheng Wu (Genes & Genomics, 2022)

Optimization of Algicidal Activity for Alteromonas sp. FDHY-03 against Harmful Dinoflagellate Prorocentrum donghaiense - Qianqian Wang; Xinguo Shi; Yisong Guo; Pin Lv; Yuying Zhong; Hui Xie; Jianfeng Chen (Journal of Marine Science and Engineering, 2022)
Prorocentrum donghaiense is a harmful-algal-bloom-forming species of planktonic dinoflagellates widely distributed around the world, which threatens the marine environment and human health. Bacteria are promising biological agents to control algal growth in HABs. Previously, we isolated an Alteromonas sp. FDHY-03, a P. donghaiense-lysing bacteria strain, from Xiapu Sea area of China. In order to improve the algicidal activity of this strain, we optimized the medium composition and culture conditions. Based on single-factor method experiment design, the optimum medium component of algicidal effect for strain FDHY-03 was sucrose and peptone. The result of Plackett–Burman design indicated that three significant factors (sucrose, peptone, and rotational speed) appeared. Finally, the concentrations of key factors were confirmed by central composite design (CCD) and response surface methodology (RSM). Under the optimized medium, the algicidal rate of strain FDHY-03 against P. donghaiense improved by 67.15%, and the OD600 value increased by 2.86-fold. The optimal source and condition were sucrose 0.46% (w/v), peptone 4.25% (w/v) addition, and rotation speed 255 rpm. Overall, this study provides an optimized method and optimum medium for improving the algicidal activity against P. donghaiense, and has a positive influence on algae-lysing bacteria for controlling the blooms of the algae in the environment.

Bioactivity-guided isolation of compounds from Sophora flavescens with antibacterial activity against Acinetobacter baumannii - Pin Li; Wern Chern Chai; Zhan-Yi Wang; Kai-Jun Tang; Jin-Yao Chen; Henrietta Venter; Susan J. Semple; Lan Xiang (Natural Product Research, 2022)

Correction to: Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Paleolimnological evidence for lacustrine environmental evolution and paleo-typhoon records during the late Holocene in eastern Taiwan - Liang-Chi Wang; Yu-Min Chou; Huei-Fen Chen; Yuan-Pin Chang; Hong-Wei Chiang; Tien-Nan Yang; Liang-Jian Shiau; Yue-Gau Chen (Journal of Paleolimnology, 2022)

Very Low Stocks and Inputs of Necromass in Wind-affected Tropical Forests - Kuo-Jung Chao; Pin-Siou Liao; Yi-Sheng Chen; Guo-Zhang Michael Song; Oliver L. Phillips; Hsing-Juh Lin (Ecosystems, 2022)

Educating Primary Care Providers and Associate Care Providers About Hepatitis C Screening of Baby Boomers: a Multi-practice Study - Bertha E. Flores; Andrea A. Fernandez; Chen-Pin Wang; Raudel Bobadilla; Ludivina Hernandez; Mamta K. Jain; Barbara J. Turner (Journal of Cancer Education, 2022)

Refractory systemic capillary leak syndrome treated with bevacizumab: a case report - Pin Wang; Chien-Hui Chan; Hsuan-Fei Chen; Woei-Yau Kao; Tzu-Rong Peng (Angiogenesis, 2022)

Magnetic porous biochar as a renewable and highly effective adsorbent for the removal of tetracycline hydrochloride in water - Hucheng Yang; Hao Yu; Jiahao Wang; Tao Ning; Pin Chen; Jing Yu; Siyuan Di; Shukui Zhu (Environmental Science and Pollution Research, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

Human health-risk assessment based on chronic exposure to the carbonyl compounds and metals emitted by burning incense at temples - Ku-Fan Chen; Yung-Pin Tsai; Chia-Hsiang Lai; Yao-Kai Xiang; Kuen-Yuan Chuang; Zhen-Hong Zhu (Environmental Science and Pollution Research, 2021)

Effect of selected sampling media, flow rate, and time on the sampling efficiency of a liquid impinger packed with glass beads for the collection of airborne viruses - Yen-Chi Chen; I-Jen Wang; Chih-Ching Cheng; Yu-Chiao Wu; Chun-Hsuan Bai; Kuo-Pin Yu (Aerobiologia, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Eliminating vascular interference from the Spot Sign contributes to predicting hematoma expansion in individuals with spontaneous cerebral hemorrhages - Pan Yi; Min Xu; Pin Chen; Yu Luo; Dongdong Wang; Hui Wang; Cunzu Wang (Acta Neurologica Belgica, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Influences of Physical Vegetation Management on Odonata Abundance in Urbanized Ecosystem: a Case Study in Northern Taiwan - Pin-Yuan Chen; Cheng-Tao Lin; Rita S. W. Yam; Hsiao-Wei Yuan (Wetlands, 2020)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Correction to: Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2020)
After publication in volume [37], issue [1], page [94–101] the authors decided to opt for Open Choice and to make the article an open access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Feasibility of using bed filters packed with rice-straw-based activated carbon and selected biomass waste for the control of frying fume exhaust - Yen-Chi Chen; Xuan-En Yang; Kun-Yi Lin; Wei-Wen Huang; Chi-Chi Lin; Kuo-Pin Yu (Environmental Science and Pollution Research, 2020)

Flavobacterium ajazii sp. nov., Isolated from Seaweed of Gouqi Island, China - Ishrat Khan; Sanjit Chandra Debnath; Cen Yan; Can Chen; Yan Xu; Wen-Jie Wang; Yu-Chao Yu; Dao-Qiong Zheng; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

Fixed-bed adsorption of copper from aqueous media using chitosan-coated bentonite, chitosan-coated sand, and chitosan-coated kaolinite - Cybelle M. Futalan; Jung-Hung Yang; Piaw Phatai; I-Pin Chen; Meng-Wei Wan (Environmental Science and Pollution Research, 2020)

Hispidulin Inhibits Neuroinflammation in Lipopolysaccharide-Activated BV2 Microglia and Attenuates the Activation of Akt, NF-κB, and STAT3 Pathway - Chung-I Yu; Cheng-I Cheng; Ya-Fei Kang; Po-Chih Chang; In-Pin Lin; Yu-His Kuo; An-Jie Jhou; Mei-Ying Lin; Chung-Yi Chen; Chien-Hsing Lee (Neurotoxicity Research, 2020)

Fish type I and type II interferons: composition, receptor usage, production and function - Zhen Gan; Shan Nan Chen; Bei Huang; Jun Zou; Pin Nie (Reviews in Aquaculture, 2020)
Interferons ( IFN s) have been reported in vertebrates from fish to mammals. To date, two types of IFN s, i.e. type I and type II IFN s have been reported in a range of fish species in aquaculture. In fish, type I IFN s are clarified into group I and group II , with two cysteines and four cysteines, and further into subgroups a, d, e, h, and b, c, f, respectively. Group I IFN s appear to exist in all fish species, whereas group II IFN s are discovered only in certain species such as cyprinids, salmonids and perciform fish. It seems preferentially functional that group I IFN s signal through cytokine receptor family B ( CRFB ) 5 and CRFB 1, while group II IFN s through CRFB 5 and CRFB 2. But they all initiate a same signalling pathway for the expression of interferon induced genes. The information about the production and the function of type I IFN s in fish are further summarized in the review. Interestingly, two members of type II IFN s, IFN ‐γ and a unique member, IFN ‐γ related gene ( IFN ‐γrel) exist in fish, and IFN ‐γ and IFN ‐γrel can separately become homodimers for signalling through CRFB 13, CRFB 17, CRFB 6 and CRFB 17, respectively. In addition, the variation in the composition of type I and type II IFN s as well as in their receptors in some cyprinid and salmonid fish has also been reviewed. It is suggested that future perspectives for the research on type I and type II IFN s in fish are outlined from a comparative and evolutionary point of view.

Transnasal endoscopic treatment on a rare case of intracranial penetrating brain injury - Min Xu; Yu Luo; Pin Chen; Pan Yi; Cun-zu Wang (Acta Neurologica Belgica, 2020)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

LncRNA TUG1 promoted osteogenic differentiation through promoting bFGF ubiquitination - Yang Yu; Ying Chen; Yi-jing Zheng; Qi-hao Weng; Si-pin Zhu; Dong-sheng Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

Correction to: Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Morphological Characterization and Gene Expression Patterns for Melanin Pigmentation in Rex Rabbit - Shuaishuai Hu; Pin Zhai; Yang Chen; Bohao Zhao; Naisu Yang; Manman Wang; Yeyi Xiao; Guolian Bao; Xinsheng Wu (Biochemical Genetics, 2019)

Critical review of ARGs reduction behavior in various sludge and sewage treatment processes in wastewater treatment plants - Gang Xue; Mingji Jiang; Hong Chen; Min Sun; Yunfan Liu; Xiang Li; Pin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Spatial Assessment of Climate Risk for Investigating Climate Adaptation Strategies by Evaluating Spatial-Temporal Variability of Extreme Precipitation - Bing-Chen Jhong; Jung Huang; Ching-Pin Tung (Water Resources Management, 2019)

Functional analysis of McSnRK1 (SNF1-related protein kinase 1) in regulating Na/K homeostasis in transgenic cultured cells and roots of halophyte Mesembryanthemum crystallinum - Hau-Hsuan Hwang; Chih-Hao Wang; Hsiao-Wei Huang; Chih-Pin Chiang; Shin-Fei Chi; Fan-Chen Huang; Hungchen E. Yen (Plant Cell Reports, 2019)

The application of forward osmosis for simulated surface water treatment by using trisodium citrate as draw solute - Shihui Yang; Baoyu Gao; Pin Zhao; Chen Wang; Xue Shen; Qinyan Yue; Ho kyong Shon (Environmental Science and Pollution Research, 2019)

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Seismic fragility and risk assessment of high-speed railway continuous-girder bridge under track constraint effect - Shengai Cui; Chen Guo; Jiao Su; Enqi Cui; Pin Liu (Bulletin of Earthquake Engineering, 2019)

Effects of a Web-based Health Education Program on Quality of Life and Symptom Distress of Initially Diagnosed Advanced Non-Small Cell Lung Cancer Patients: A Randomized Controlled Trial - Chi-Chin Huang; Han-Pin Kuo; Yueh-E Lin; Shu-Ching Chen (Journal of Cancer Education, 2019)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Evaluating Future Joint Probability of Precipitation Extremes with a Copula-Based Assessing Approach in Climate Change - Bing-Chen Jhong; Ching-Pin Tung (Water Resources Management, 2018)

Anti-Oxidative Effects of Melatonin Receptor Agonist and Omega-3 Polyunsaturated Fatty Acids in Neuronal SH-SY5Y Cells: Deciphering Synergic Effects on Anti-Depressant Mechanisms - Senthil Kumaran Satyanarayanan; Yin-Hwa Shih; Yu-Chuan Chien; Shih-Yi Huang; Piotr Gałecki; Siegfried Kasper; Jane Pei-Chen Chang; Kuan-Pin Su (Molecular Neurobiology, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Analyzing gravity anomaly variations before the 2016 Ms 6.4 earthquake in Menyuan, Qinghai with an interpolation/cutting potential field separation technique - Jin-Zhao Liu; Tong-Qing Wang; Zhao-Hui Chen; Pin Zhang; Chuan-Dong Zhu; Shuang-Xi Zhang (Applied Geophysics, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Assessing climate change adaptations for community-scale water resources using a low-frequency weather generator - Yuan-Hua Li; Ching-Pin Tung; Yuan-Hung Li; Pei-Yuan Chen (Paddy and Water Environment, 2018)

Transcriptome comparative analysis of two Camellia species reveals lipid metabolism during mature seed natural drying - Jin-Ling Feng; Zhi-Jian Yang; Wei-Wei Bai; Shi-Pin Chen; Wen-Qiang Xu; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Rice yield development and the shrinking yield gaps in China, 1981–2008 - Yi Chen; Pin Wang; Zhao Zhang; Fulu Tao; Xing Wei (Regional Environmental Change, 2017)

Photocatalytic decomposition of indoor ozone motivated by the white-light-emitting diode - Jia-You Gong; Yen-Chi Chen; Kuo-Pin Yu (Clean Technologies and Environmental Policy, 2017)

Future extreme temperature and its impact on rice yield in China - Zhao Zhang; Yi Chen; Chenzhi Wang; Pin Wang; Fulu Tao (International Journal of Climatology, 2017)
Rice in China is increasingly suffered from extreme temperature stress ( ETS ) with ongoing climate change. It is projected that ETS would increase notably across the world in the future. However, the spatio‐temporal change of ETS in main rice planting areas in China is still unclear; and the future yield loss caused by ETS ( YL ETS ) has seldom been investigated quantitatively. In this study, we first investigated the spatio‐temporal change of ETS across China under 20 climate change scenarios consisting of five global climate models and four Representative Carbon Pathways (2.6, 4.5, 6.0, and 8.5). Then, using a process‐based crop model ( MCWLA ‐Rice), its 30 sets of model parameters and the 20 climate change scenarios, we conducted a super‐ensemble assessment to investigate the YL ETS over 2020–2049, relative to the baseline period (1980–2009), across China. The results showed that, an increased heat ETS and a decreased cold ETS would be expected for most areas. As a result, a large spatial variability of yield loss would be expected in the future, including severely cold stress for region I (northeastern China, single rice) and region IV (southern China, early rice), but severely heat stress for region III (the middle and lower reaches of Yangtze River, single rice) and region IV (southern China, late rice). Comparing yield loss from both ETS , a decreased change in yield loss would be mainly expected in region I (northeastern China, single rice), while an increased change for region III (the middle and lower reaches of Yangtze River, single rice) and IV (southern China, late rice), with less change for region II (southwestern China, single rice) and IV (southern China, early rice). Finally, some adaptation measures were proposed for the ETS ‐sensitive areas. Our findings are useful to develop effective policies to cope with climate risk and relieve ETS disasters.

Signaling pathway in development of Camellia oleifera nurse seedling grafting union - Jin-Ling Feng; Zhi-Jian Yang; Shi-Pin Chen; Yousry A. El-Kassaby; Hui Chen (Trees, 2017)

Nonlinear biotic ligand model for assessing alleviation effects of Ca, Mg, and K on Cd toxicity to soybean roots - Bo-Ching Chen; Pin-Jie Wang; Pei-Chi Ho; Kai-Wei Juang (Ecotoxicology, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2017)
Exogenous crosslinking has been shown to have potential for treating disc degeneration and back pain due to its ability to increase the strength and toughness of the annulus fibrosus, increase intervertebral joint stability, decrease intradiscal pressure, and increase fluid flow through the disc. Some results imply that crosslink augmentation may also lead to changes in the compressive load sharing properties of the disc. The objective of the present study was to evaluate directional stress distribution changes of the disc following genipin crosslinking treatment. Bovine lumbar motion segments were randomly divided into control and crosslinked groups. Annular strains were determined from simultaneous deformation measurements at various time points during compressive creep testing. Four stress components of the annulus were then calculated according to the previously measured modulus data. Immediately after the application of a 750-N compressive load, mean axial and radial compressive stresses in the crosslinked group were twofold higher than control means. Conversely, mean lamellae-aligned and circumferential tensile stresses of the crosslinked discs were 8- and threefold lower, respectively, compared to control means. After 1-h creep loading, the two compressive mean stresses in both the control and genipin-crosslinked specimens increased approximately threefold from their initial 750-N-loaded values. The two tensile mean stresses in the crosslinked group remained lower than the respective levels of the control means after creep loading. A greater proportion of annular compressive load support under compressive creep loading, with a commensurate decrease in both tensile stresses and strains, was seen in the discs following exogenous crosslink augmentation.

Dietary silymarin supplementation promotes growth performance and improves lipid metabolism and health status in grass carp (Ctenopharyngodon idellus) fed diets with elevated lipid levels - Peizhen Xiao; Hong Ji; Yuantu Ye; Baotong Zhang; Yongsheng Chen; Jingjing Tian; Pin Liu; Liqiao Chen; Zhenyu Du (Fish Physiology and Biochemistry, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction - Yang Chen; Lei Wang; Ashley L. Pitzer; Xiang Li; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2016)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

A new species of Rhinogobius (Teleostei: Gobiidae) from Zhejiang Province, China - Shih-Pin Huang; I-Shiung Chen; Kwang-Tsao Shao (Ichthyological Research, 2016)

Erratum to: The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

The phylogenetic and recombinational analysis of beak and feather disease virus Taiwan isolates - Shr-Wei Huang; Yu-Chung Chiang; Chien-Yu Chin; Pin-Chi Tang; Pan-Chen Liu; Chi-Young Wang (Archives of Virology, 2016)

A sudden cardiac asystole and cardiopulmonary resuscitation of trigeminocardiac reflex during retrosigmoid approach surgery - Xu Min; Bo Jixiang; Chen Pin; Wang Cunzu (Acta Neurologica Belgica, 2016)

Imaging Rainfall Infiltration Processes with the Time-Lapse Electrical Resistivity Imaging Method - Gang Zhang; Gui-Bin Zhang; Chien-chih Chen; Ping-Yu Chang; Tzu-Pin Wang; Horng-Yuan Yen; Jia-Jyun Dong; Chuen-Fa Ni; Su-Chin Chen; Chao-Wei Chen; Zheng-yuan Jia (Pure and Applied Geophysics, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

How much yield loss has been caused by extreme temperature stress to the irrigated rice production in China? - Pin Wang; Zhao Zhang; Yi Chen; Xing Wei; Boyan Feng; Fulu Tao (Climatic Change, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Potential assessment on gas turbine combined cycle with alternative gaseous fuel from coal gasification - Yau-Pin Chyou; Hsiu-Mei Chiu; Po-Chuang Chen (Clean Technologies and Environmental Policy, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

A rare self-injurious case of multiple penetrating brain injury by nails in a young patient with depressive disorder - Min Xu; Jinkun Wen; Xun Zhu; Pin Chen; Cunzu Wang (Acta Neurologica Belgica, 2015)

A New Schiff Base Chemodosimeter for Fluorescent Imaging of Ferric Ions in Living Cells - Yan-Zi Chen; Yeshwant Ramchandra Bhorge; Albert J. Pape; Rupesh D. Divate; Yun-Chin Chung; Yao-Pin Yen (Journal of Fluorescence, 2015)

Subgroups of US IRAQ and Afghanistan veterans: associations with traumatic brain injury and mental health conditions - Carlos A. Jaramillo; Douglas B. Cooper; Chen-Pin Wang; David F. Tate; Blessen C. Eapen; Gerald E. York; Mary Jo Pugh (Brain Imaging and Behavior, 2015)

Dynamic variability of the heading–flowering stages of single rice in China based on field observations and NDVI estimations - Zhao Zhang; Xiao Song; Yi Chen; Pin Wang; Xing Wei; Fulu Tao (International Journal of Biometeorology, 2015)

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

The spatio-temporal variations of surface water quality in China during the “Eleventh Five-Year Plan” - Jingbo Sun; Yi Chen; Zhao Zhang; Pin Wang; Xiao Song; Xing Wei; Boyan Feng (Environmental Monitoring and Assessment, 2015)

A novel SMAD family protein, SMAD9 is involved in follicular initiation and changes egg yield of geese via synonymous mutations in exon1 and intron2 - Jun Xu; Jun Li; Haosen Wang; Guanglin Wang; Jie Chen; Pin Huang; Jienan Cheng; Lu Gan; Zhao Wang; Yafei Cai (Molecular Biology Reports, 2015)

Integrated water resources system dynamics modeling and indicators for sustainable rural community - Yuan-Hua Li; Pei-Yuan Chen; Wei-Hsuan Lo; Ching-Pin Tung (Paddy and Water Environment, 2015)

Probabilistic framework for assessing the arsenic exposure risk from cooked fish consumption - Min-Pei Ling; Chiu-Hua Wu; Szu-Chieh Chen; Wei-Yu Chen; Chia-Pin Chio; Yi-Hsien Cheng; Chung-Min Liao (Environmental Geochemistry and Health, 2014)

The evolution of permeability and gas composition during remote protective longwall mining and stress-relief gas drainage: a case study of the underground Haishiwan Coal Mine - Wei Li; Yuan-ping Cheng; Pin-kun Guo; Feng-hua An; Ming-yi Chen (Geosciences Journal, 2014)

Temperature variations and rice yields in China: historical contributions and future trends - Pin Wang; Zhao Zhang; Xiao Song; Yi Chen; Xing Wei; Peijun Shi; Fulu Tao (Climatic Change, 2014)

Spatial pattern and decadal change of agro-meteorological disasters in the main wheat production area of China during 1991–2009 - Zhao Zhang; Pin Wang; Yi Chen; Shuai Zhang; Fulu Tao; Xiaofei Liu (Journal of Geographical Sciences, 2014)

Spatial and temporal changes of agro-meteorological disasters affecting maize production in China since 1990 - Zhao Zhang; Yi Chen; Pin Wang; Shuai Zhang; Fulu Tao; Xiaofei Liu (Natural Hazards, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

The heat deficit index depicts the responses of rice yield to climate change in the northeastern three provinces of China - Zhao Zhang; Xiaofei Liu; Pin Wang; Jiabing Shuai; Yi Chen; Xiao Song; Fulu Tao (Regional Environmental Change, 2014)

Spatiotemporal changes of global extreme temperature events (ETEs) since 1981 and the meteorological causes - Xiao Song; Zhao Zhang; Yi Chen; Pin Wang; Ming Xiang; Peijun Shi; Fulu Tao (Natural Hazards, 2014)

A study of earthquake inter-occurrence times distribution models in Taiwan - Chi-Hsuan Chen; Jui-Pin Wang; Yih-Min Wu; Chung-Han Chan; Chien-Hsin Chang (Natural Hazards, 2013)

Liquid–liquid equilibrium (LLE) study for six-component transesterification system - Pin Pin Oh; Mei Fong Chong; Harrison Lik Nang Lau; Junghui Chen; Yuen May Choo (Clean Technologies and Environmental Policy, 2013)

The optimal fractional Gabor transform based on the adaptive window function and its application - Ying-Pin Chen; Zhen-Ming Peng; Zhen-Hua He; Lin Tian; Dong-Jun Zhang (Applied Geophysics, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

The integration of nautical hazard assessment and harbor GIS models to the Taichung Port area in Taiwan - Cheng-Wu Chen; Ching-Chung Lee; Chia-Hung Chen; Chun-Pin Tseng (Natural Hazards, 2013)

Increasing concentrations of aerosols offset the benefits of climate warming on rice yields during 1980–2008 in Jiangsu Province, China - Jiabing Shuai; Zhao Zhang; Xiaofei Liu; Yi Chen; Pin Wang; Peijun Shi (Regional Environmental Change, 2013)

Application of GIS for the determination of hazard hotspots after direct transportation linkages between Taiwan and China - Cheng-Wu Chen; Ching-Chung Lee; Chun-Pin Tseng; Chia-Hung Chen (Natural Hazards, 2013)

Impact of chilling injury and global warming on rice yield in Heilongjiang Province - Xiaofei Liu; Zhao Zhang; Jiabing Shuai; Pin Wang; Wenjiao Shi; Fulu Tao; Yi Chen (Journal of Geographical Sciences, 2013)

A new viewpoint of hazard assessment and management for Taiwan’s insurance issues - Cheng-Wu Chen; Kevin Fong-Rey Liu; Meng-Lung Lin; Chun-Pin Tseng (Natural Hazards, 2013)

A procedure to estimate cover coefficient and parameters of soil moisture stress function using soil moisture monitoring data - Nien-Ming Hong; Ching-Pin Tung; Chu-hui Chen (Paddy and Water Environment, 2013)

Hazard management and risk design by optimal statistical analysis - Cheng-Wu Chen; Kevin Fong-Rey Liu; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

A novel strategy to determine the insurance and risk control plan for natural disaster risk management - Cheng-Wu Chen; Chun-Pin Tseng; Wen-Ko Hsu; Wei-Ling Chiang (Natural Hazards, 2012)

Surface-functionalization effects on uptake of fluorescent polystyrene nanoparticles by model biofilms - Brian A. Nevius; Yung Pin Chen; John L. Ferry; Alan W. Decho (Ecotoxicology, 2012)

Default risk-based probabilistic decision model for risk management and control - Cheng-Wu Chen; Chun-Pin Tseng (Natural Hazards, 2012)

Study on agricultural benefits by increasing capacity of water ponds: a case study at Taoyuan paddy fields - Wen-Tsun Fang; Chuan-Pin Chien; Shu-Chen Chen (Paddy and Water Environment, 2012)

Identification of Putative Artemisia annua ABCG Transporter Unigenes Related to Artemisinin Yield Following Expression Analysis in Different Plant Tissues and in Response to Methyl Jasmonate and Abscisic Acid Treatments - Ling Zhang; Xu Lu; Qian Shen; Yunfei Chen; Tao Wang; Fangyuan Zhang; Shaoyan Wu; Weimin Jiang; Pin Liu; Lida Zhang; Yueyue Wang; Kexuan Tang (Plant Molecular Biology Reporter, 2012)

Bioaccumulation and Toxicodynamics of Cadmium to Freshwater Planarian and the Protective Effect of N-Acetylcysteine - Jui-Pin Wu; Hon-Cheng Chen; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2012)

Increased susceptibility of algal symbionts to photo-inhibition resulting from the perturbation of coral gastrodermal membrane trafficking - Chii-Shiarng Chen; Shih-Pin Yeh; Li-Hsueh Wang; Hsing-Hui Li; Uang Wan-Nan Chen (Science China Life Sciences, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Risk and uncertainty analysis in the planning stages of a risk decision-making process - Wen-Ko Hsu; Chun-Pin Tseng; Wei-Ling Chiang; Cheng-Wu Chen (Natural Hazards, 2012)

Natural disaster management mechanisms for probabilistic earthquake loss - Chun-Pin Tseng; Cheng-Wu Chen (Natural Hazards, 2012)

A new viewpoint on risk control decision models for natural disasters - Chun-Pin Tseng; Cheng-Wu Chen; Yu-Ping Tu (Natural Hazards, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Detection and identification of a new phytoplasma associated with periwinkle leaf yellowing disease in Taiwan - Wuu-Yang Chen; Yao-Chen Huang; Meng-Lu Tsai; Chan-Pin Lin (Australasian Plant Pathology, 2011)

DPP4 deficiency preserves cardiac function via GLP-1 signaling in rats subjected to myocardial ischemia/reperfusion - Hui-Chun Ku; Wen-Pin Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Prazosin induces p53-mediated autophagic cell death in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Yuh-Lien Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

Pnn and SR family proteins are differentially expressed in mouse central nervous system - Shu-Yuan Hsu; Yen-Jung Chen; Pin Ouyang (Histochemistry and Cell Biology, 2011)

GLP-1 signaling preserves cardiac function in endotoxemic Fischer 344 and DPP4-deficient rats - Hui-Chun Ku; Wen-Pin Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Thaliporphine ameliorates cardiac depression in endotoxemic rats through attenuating TLR4 signaling in the downstream of TAK-1 phosphorylation and NF-κB signaling - Wen-Pin Chen; Hsiao-Jung Tzeng; Hui-Chun Ku; Yi-Jin Ho; Shoei-Sheng Lee; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Assessing the phytotoxicity of chromium in Cr(VI)-spiked soils by Cr speciation using XANES and resin extractable Cr(III) and Cr(VI) - Chiou-Pin Chen; Kai-Wei Juang; Tzu-Huei Lin; Dar-Yuan Lee (Plant and Soil, 2010)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

Appraisal of affordable green subsidy of rice paddy in Taiwan - Chen-Wuing Liu; Shih-Wei Zhang; Hsing-Pin Yao; Kuo-Hua Lin; Wei-Taw Lin (Paddy and Water Environment, 2010)

Anticancer activity of a cyclooxygenase inhibitor, CX9051, in human prostate cancer cells: the roles of NF-κB and crosstalk between the extrinsic and intrinsic apoptotic pathways - Chiung-Hua Huang; Jih-Hwa Guh; Grace Shiahuy Chen; Pin-Hsuan Lu; Ji-Wang Chern (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Transforming growth factor-β type I receptor/ALK5 contributes to doxazosin-induced apoptosis in H9C2 cells - Yi-Fan Yang; Chau-Chung Wu; Wen-Pin Chen; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Joint Impact of Scaling and Hysteresis on NAPL Flow Simulation - Hung-Hui Chen; Liang-Cheng Chang; Hsin-Yu Shan; Jui-Pin Tsai (Environmental Modeling & Assessment, 2009)

Isolation and characterization of 30 novel polymorphic microsatellite loci from Japanese halfbeak, Hyporhamphus sajori (Temminck et Schlegel, 1846) - Shi-Chao Xing; Gen-Bo Xu; Guan-Pin Yang; Shan-Shan Liu; Xiao-Lin Liao; Yong-sheng Tian; Song-Lin Chen (Conservation Genetics, 2009)

The last 100 000 years' palaeoenvironmental changes inferred from the diatom assemblages of core MD012404 from the Okinawa Trough, East China Sea - Yuan‐Pin Chang; Wei‐Lung Wang; Min‐Te Chen (Journal of Quaternary Science, 2009)
The diatom assemblage records preserved in a sedimentary core MD012404 retrieved from the Okinawa Trough in the East China Sea (ECS) imply palaeoenvironmental changes of the last 100 ka. Our statistical analyses of diatom species abundance data indicate that the assemblages dominate open ocean and warm water, coastal water and freshwater masses in the ECS. These proxy species were used to infer the long‐term variation in surface hydrological conditions and palaeoclimate. Cycles of ca. 23 ka observed in the relative abundance of the tychopelagic species Paralia sulcata indicate that the increases in precipitation driven by solar insolation might have controlled the diatom assemblages in the ECS. The diatom records also indicate relatively low abundances of tropical, tychopelagic and freshwater species during millennial‐scale cold events such as the Younger Dryas and Heinrich events, which have been well expressed in the high‐latitude Northern Hemisphere climate. The floral patterns are interpreted as synchronous cooling and more saline sea surface conditions in the ECS caused by the enhanced Asian winter monsoon during the Northern Hemisphere cold events. The higher abundances of tropical species during deglaciation and the Holocene might have been linked to gradual increases in the inflow of the Kuroshio into the Okinawa Trough. The records also suggest a temporary reduction in tropical species from 5 to 3 ka, corresponding to the Pulleniatina Minimum Event during which the warm‐water planktic foraminifer Pulleniatina obliquiloculata was rare. Copyright © 2009 John Wiley & Sons, Ltd.

Isolation and Characterization of New Maize B Sequences from a Microdissected Library - Kuan-lin Lo; Yao-pin Lin; Liang-jwu Chen; Bor-yaw Lin (Plant Molecular Biology Reporter, 2009)

The taxonomy and phylogeny of the cyprinid genus Opsariichthys Bleeker (Teleostei: Cyprinidae) from Taiwan, with description of a new species - I-Shiung Chen; Jui-Hsien Wu; Shih-Pin Huang (Environmental Biology of Fishes, 2009)

Dual-rhodamine urea derivative, a novel chemidosimeter for Hg(II) and its application in imaging Hg(II) in living cells - Pin-xian Xi; Liang Huang; Heng Liu; Peng-fei Jia; Feng-juan Chen; Min Xu; Zheng-zhi Zeng (JBIC Journal of Biological Inorganic Chemistry, 2009)

Twelve polymorphic microsatellite loci from a dinucleotide-enriched genomic library of Japanese Spanish mackerel (Scomberomorus niphonius) - Shi-Chao Xing; Gen-Bo Xu; Xiao-Lin Liao; Guan-Pin Yang; Song-Lin Chen (Conservation Genetics, 2009)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Differential global genomic changes in rice root in response to low-, middle-, and high-osmotic stresses - Ting-chen Ma; Rong-jun Chen; Rong-rong Yu; Han-lai Zeng; Duan-pin Zhang (Acta Physiologiae Plantarum, 2009)

Synthesis, Characterization, Antioxidant Activity and DNA-Binding Studies of Three Rare Earth (III) Complexes with 1-(4-Aminoantipyrine)-3-tosylurea Ligand - Pin-xian Xi; Zhi-hong Xu; Xiao-hui Liu; Feng-juan Chen; Zheng-zhi Zeng; Xiao-wen Zhang; Ying Liu (Journal of Fluorescence, 2009)

Co-circulating genetically divergent A2 human metapneumovirus strains among children in southern Taiwan - Hsuan-Chen Wang; Sheng-Wen Huang; Shainn-Wei Wang; Huey-Pin Tsai; David Kiang; Shih-Min Wang; Ching-Chuan Liu; Ih-Jen Su; Jen-Ren Wang (Archives of Virology, 2008)

Non-monophyly of fish in the Sinipercidae (Perciformes) as inferred from cytochrome b gene - Dali Chen; Xianguang Guo; Pin Nie (Hydrobiologia, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Detection and identification of the phytoplasma associated with pear decline in Taiwan - Hsiu-Lin Liu; Ching-Chung Chen; Chan-Pin Lin (European Journal of Plant Pathology, 2007)

Assessing Genetic Diversity of Chinese Cultivated Barley by STS Markers - Xiwen Chen; Shaoying Guo; Defu Chen; Pin Liu; Xiangdong Jia; Lijun Sun (Genetic Resources and Crop Evolution, 2006)

Gene structure and transcription of IRF-2 in the mandarin fish Siniperca chuatsi with the finding of alternative transcripts and microsatellite in the coding region - Baojian Sun; Mingxian Chang; Dali Chen; Pin Nie (Immunogenetics, 2006)

Assessing Impacts of Typhoons and the Chi-Chi Earthquake on Chenyulan Watershed Landscape Pattern in Central Taiwan Using Landscape Metrics - Yu-pin Lin; Tsun-kuo Chang; Chen-fa Wu; Te-chih Chiang; Shin-hwei Lin (Environmental Management, 2006)

Using the Selective Ion Exchange Resin Extraction and XANES Methods to Evaluate the Effect of Compost Amendments on Soil Chromium(VI) Phytotoxicity - Dar-Yuan Lee; Yu-Na Shih; Hsiu-Ching Zheng; Chiou-Pin Chen; Kai-Wei Juang; Jyh-Fu Lee; Lo Tsui (Plant and Soil, 2006)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Characterization of the genomic structures and selective expression profiles of nine class I small heat shock protein genes clustered on two chromosomes in rice (Oryza sativa L.) - Jiahn-Chou Guan; Tsung-Luo Jinn; Ching-Hui Yeh; Shi-Pin Feng; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 2004)

Double-strand hydrolysis of DNA by a magnesium(II) complex with diethylenetriamine - Pin Yang; Rui Ren; Maolin Guo; Aixin Song; Xiangli Meng; Caixia Yuan; Qinghua Zhou; Huili Chen; Zhenhai Xiong; Xiaoli Gao (JBIC Journal of Biological Inorganic Chemistry, 2004)

Molecular assay of novel pasturage, sugarcane-grass 94-42, using RAPD markers - Chen Liang; Lin Nan; Huang Zhen; Weng Pin; Lu Chuanbei; Shen Mingshan (Genetic Resources and Crop Evolution, 2004)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Hydrogen peroxide enhanced inron-induced injury in isolated heart and ventricular cardiomyocyte in rats - Ying Ying Che Chen; Kwok Pin Ho; Qiang Xia; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2002)

DNA probes and PCR primers for the detection of a phytoplasma associated with peanut witches'-broom - Miaw-Fan Chen; Chan-Pin Lin (European Journal of Plant Pathology, 1997)

Purification and properties of a homodimeric protocatechuate 4,5-dioxygenase from Rhizobium leguminosarum - Yung Pin Chen; Charles R. Lovell (Archives of Microbiology, 1994)

Purification and properties of a homodimeric protocatechuate 4,5-dioxygenase from Rhizobium leguminosarum - Yung Pin Chen; Charles R. Lovell (Archives of Microbiology, 1994)

Utilization of aromatic compounds as carbon and energy sources during growth and N2-fixation by free-living nitrogen fixing bacteria - Yung Pin Chen; Geralyne Lopez-de-Victoria; Charles R. Lovell (Archives of Microbiology, 1993)